PENJATUHAN TALAK MELALUI APLIKASI WHATSAPP DITINJAU DARI HUKUM ISLAM DAN HUKUM POSITIF - Hilman Kamiludin (An-Nahdliyyah: Jurnal Studi Keislaman, 2023)
The pronouncement of divorce is crucial as it is related to the validity of the divorce. The advancement of time, especially field of information and communication technology, has even penetrated into the realm of households. One intriguing aspect to investigate is the legal implications of pronouncing divorce through platforms like WhatsApp. From a legal perspective, there are differences between Islamic law and Positive law regarding divorce. This research aims to provide an understanding of the meaning and regulations of divorce and the pronouncement of divorce in both Islamic and Positive law through analysis and examination of various references as data sources in literature research. According to the scholars following the Syafi'i school of thought, the legal status of divorces conveyed through WhatsApp, SMS, Facebook, Instagram, and other social media is considered and viewed similarly to written divorces. Divorces declared or conveyed online can be deemed valid even though the person involved may not pronounce it verbally. However, according to Positive law, the pronouncement of divorce through WhatsApp is not valid because it falls outside the jurisdiction a court hearing. The pronouncement of divorce by a husband or his representative must be made in the presence of a court hearing.